How to Test the Anterolateral Ligament With Ultrasound - Cavaignac, Etienne (Arthrosc Tech, 2017)
Ultrasonography (US) is a nonirradiating, low-cost, real-time imaging modality that has very good spatial resolution. US can be used to view the anterolateral ligament (ALL) and injuries to the ALL. Several authors have sought to analyze the anterolateral aspect of the knee using US with varying luck. All of them analyzed the ALL statically only. The goal of this Technical Note is to describe in detail the technique that we use to analyze the anterolateral aspect of the knee in patients with an anterior cruciate ligament tear. We use a simple technique that starts by locating the tibial end of the ALL. The lateral inferior genicular artery is a reliable landmark in this context. The analysis is dynamic in addition to being static. To determine if the ALL is injured, we look for a lack of tension on the ALL when the knee is internally rotated and for a Segond fracture. We believe that it is essential to start evaluating the ALL by its tibial end. US analysis of the ALL forms the basis for developing an appropriate “à la carte” treatment for the patient's injury.